3,000 km and 1,500‐year presence of Aureococcus anophagefferens reveals indigenous origin of brown tides in China - Ying Zhong Tang; Zhaopeng Ma; Zhangxi Hu; Yunyan Deng; Aoao Yang; Siheng Lin; Liang Yi; Zhaoyang Chai; Christopher J. Gobler (Molecular Ecology, 2019)
The nonmotile, spherical, picoplanktonic (2‐μm‐sized) pelagophyte Aureococcus anophagefferens has caused numerous harmful blooms (“brown tides”) across global marine ecosystems. Blooms have developed along the east coast of the USA since 1985, a limited number of times in South Africa around 1997, and frequently in China since 2009. As a consequence, the harmful blooms have caused massive losses in aquaculture and coastal ecosystems, particularly mortalities in cultured shellfish. Therefore, whether A. anophagefferens was recently introduced to China via natural/artificial transport of resting stage cells or has been an indigenous species has become a question of profound ecological significance and broad interest, which motivated our extensive investigation on the geographic and historical presence of this species in the seas of China. We applied a combined approach of extensive PCR‐based detection and sequencing, germination experiments and monoclonal antibody staining of germlings to samples of surface sediment and sediment core (dated via combined isotopic measurements) collected from all four seas of China, and searched the supplementary data set of a recent Science publication. We discovered that A. anophagefferens does have a resting stage in the sediment, but it also has a wide geographic distribution both in China (covering a range of ~30° in latitude, ~15.7° in longitude and 2.5–3,456 m in water depth; temperate to tropical and coastal to open oceans) and in almost all oceans of the world and a historical presence of >1,500 years in the Bohai Sea, China. The work revealed that A. anophagefferens is not a recently introduced, but an indigenous species in China and has in fact a globally cosmopolitan distribution.